Lignocaine in Migraine Treatment: A Comprehensive Review - Jakub Kalisiak; Max Tschuschke; Martyna Choinka; Mikołaj Lorenz; Jędrzej Lewandowski; Agata Konopka; Zuzanna Szczepaniak; Natalia Wdowiak; Małgorzata Komarów; Dominika Karasińska (Quality in Sport, 2024)
Introduction: Migraine is a prevalent and debilitating neurological disorder characterized by recurrent headaches and associated symptoms such as nausea, photophobia, and phonophobia. While conventional treatments exist, a significant subset of patients suffers from refractory migraines, prompting the exploration of alternative therapies like lignocaine.